Hemiodus jatuarana, a new species of Hemiodontidae from the rio Trombetas, Amazon Basin, Brazil (Teleostei, Characiformes) - Langeani, F. (Magnolia Press, 2004)
Hemiodus jatuarana, a new species of the Hemiodontidae from Oriximina, rio Trombetas, Amazon Basin, Brazil, is described. The new species can be readily distinguished from its congeners by the presence of a horizontally elongated dark spot on the caudal peduncle, and by the absence of any other dark pigmentation pattern on the body. Hemiodus jatuarana is readily separated from H. immaculatus, another species without dark pigmentation on the body, by having 25 - 27 epibranchial and 36 - 37 ceratobranchial gill rakers on the first branchial arch, and caudal-fin lobes without longitudinal stripes, vs. 14 - 16 and 21 - 25 gill rakers, and a conspicuous longitudinal stripe on each caudalfin lobe in H. immaculatus. The new species is only known from its type-locality, where it cooccurs with H. immaculatus.
Keywords: Teleostei; Characiformes; Hemiodontidae; Hemiodus; new species; rio Trombetas; Amazon basin